SHADOW4: the popular ray tracing revived for evolving synchrotron sources in fourth-generation storage rings - del Rio, Manuel Sanchez; Reyes-Herrera, Juan; Shi, Xianbo; Rebuffi, Luca (Journal of physics. Conference series, 2025)
We present SHADOW4, a new version of the popular ray tracing code. The SHADOW kernel has been completely rewritten in Python applying modern concepts of software engineering. A new user interface is available in the OASYS ecosystem. The new tool has been designed and implemented preparing the future needs both in computing (cloud computing, AI integration) and in the transit to fourth generation sources and beyond.